FINITE-ELEMENT METHOD FOR THE MODEL PSEUDOPARABOLIC EQUATION - Lotfikar, R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper the construction of the approximate solution to the initialboundary value problem for the pseudoparabolic equation using finite-element method is considered. It is proved that the costructed sequence converges to the exact solution and error estimate is obtained.